Daily field checking list by Walter Rosene, March 23, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bob Walker, March 23, 1937. Also notes there were numerous American Robins, Eastern Meadowlarks, Common Grackles, Red-winged Blackbirds, Dark-eyed Juncos and Killdeers in the area. Plustek--flatbed